APPLICATION OF FUZZY MULTIPLE CRITERIA DECISION MAKING (MCDM) IN SELECTION OF PROSPECTIVE EMPLOYEES - Sutrisno Sutrisno; Sutikno Wahyu Hidayat; Avando Bastari; Okol Sri Suharyo (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2019)
The recruitment process is the initial process that determines the sustainability and success of a company. In the process, effective and efficient selection tests are the key. The level of professionalism and academic ability of prospective employees are two things that are very much needed as a reference and criteria that are used as selection factors in the recruitment process. This study uses the Fuzzy Multiple Criteria Decision Making (MCDM) method by solving problems using the Simple Addictive Weighting Method (SAW). The use of this method is expected to produce an electronic selection test application that can help the recruitment team in carrying out the selection process at PT. X. The results of the research are in the form of prospective employee selection test applications to simplify the process of selecting prospective employees according to their needs. Keywords: Selection Test, Application, FMCDM, SAW